Enough is Enough: A Novella Exploring the Effects of Bullying on a Young Adult - Jeanie Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This creative work explores the effects of bullying on a young adult, highlighting its mostly negative effects on a young adult in a high school setting. Bullying is often described as an act of inflicting distress towards a weaker individual done by a stronger individual. The act of bullying can be found everywhere, but it is especially prevalent in academic settings, from elementary school up to university. Through Satria’s point of view, this novella aims to raise awareness about the negative effects of bullying towards a young adult who is different from others. Satria experiences different negative effects of bullying, including depression, loneliness, and helplessness because of the difference between him and his classmates. Through his hobbies and close relationship with Indra, Satria manages to cope with the negative effects of bullying. This work aims to offer a different view and approach towards the negative effects of bullying.